Implementation of isoniazid preventive therapy in southern Lima, Peru: an analysis of health center characteristics - Roberto Zegarra-Chapoñan; Lily Victoria Bonadonna; Courtney M. Yuen; Martha Brigida Martina-Chávez; Jhon Zeladita-Huaman (BMC, 2021)
Abstract Background Tuberculosis (TB) prevention through the use of preventive treatment is a critical activity in the elimination of TB. In multiple settings, limited staffing has been identified as a barrier to managing preventive treatment for TB contacts. This study aims to determine how health center staffing, service type, and TB caseload affects implementation of isoniazid preventive therapy (IPT) for TB contacts in southern Lima. Methods We conducted an ecological study in 2019 in southern Lima, Peru. Through the review of medical records, we identified contacts of TB patients who initiated IPT during 2016-2018, and who were 0-19 years old, the age group eligible for IPT according to Peruvian guidelines. We assessed bivariate associations between health center characteristics (numbers of physicians and nurses, types of services available, annual TB caseload) and IPT initiation and completion using binomial logistic regression. Results Among 977 contacts, 69% took more than a week to start IPT and 41% did not complete IPT. For those who successfully completed IPT, 58% did not complete full medical follow-up. There was no significant difference in IPT completion or adherence based on whether health centers had more physicians and nurses, more comprehensive services, or higher TB caseloads. Among contacts, female sex was associated with delay in initiating IPT (P = 0.005), age 5-19 years old was associated with completion of IPT (P = 0.025) and age < 5 years old was associated with completion of clinical evaluations (P = 0.041). Conclusions There are significant gaps in IPT implementation in health centers of southern Lima, Peru, but insufficient staffing of health centers may not be responsible. Further research is needed to identify how IPT implementation can be improved, potentially through improving staff training or monitoring and supervision. Graphic abstract